مفهوم التّخطيط الاستراتيجيّ اللّغويّ للّغة العربيّة: The concept of linguistic strategic planning for the Arabic language - Abbass Elaimam, Amal Mussa (SIBAWAYH Arabic Language and Education, 2020)
This study aims to crystallize the concept of linguistic strategic planning from a number of concepts scattered and deposit it in the corridors of linguistic literature in a precise way, whose idea began to take a strong step in the educational administrative structures until the planning of the lessons arrived. The study asked several questions, the most important of which are: How can a conceptual and strategic planning for the linguistic language of the Arabic language be elaborated and formulated from a set of disjointed and scattered concepts in linguistic literature that implies its meanings, and from among the concepts around it? What is strategic planning? What are the conditions and reality of the Arabic language? The study used the descriptive approach and addressed the topic according to: The definition of strategic planning and the conditions of the Arabic language in the Arab world. Deals with the definition of concepts (linguistic planning - linguistic policies - linguistic identity - linguistic security - linguistic globalization - linguistic strategic planning) and from there the concept of linguistic strategic planning for the Arabic language is elaborated. Among the most important results: the linguistic strategic planning of the Arabic language expands to include all the terms circulating in the corridors of linguistic literature, linguistic policies - linguistic planning - linguistic globalization - language security. The concept of linguistic security of the Arabic language is one of the most dangerous concepts that fall under the strategic linguistic planning of the Arabic language. It is directly based on it, but it is not discussed in the corridors of language studies in a way that shows the significance of the significand.